2009
DOI: 10.5539/ies.v2n3p3
|View full text |Cite
|
Sign up to set email alerts
|

Promising Practice of Technology Integration in Math and Science Instruction: A Case of California Charter High School

Abstract: This study was conducted to examine the promising practice of using technology in teaching math and science in a charter high school in California. The research employed an in-depth qualitative case study method. The main participants were principals, lead teachers, teachers, and support staff. Interviews, observations, and archival documents were the main data collection tools. The study found that the practice of using technology in teaching by the school, Center for Advanced Research and Technology (CART), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In kindergarten through grade 12 mathematics education, technology is viewed as an integral part of instruction. There is evidence to support the positive impact technology has on mathematics achievement (Cheung & Slavin, 2013;Eyyam & Yaratan, 2014;Ojose, 2009;Schacter, 1999;Weaver, 2000;Zhang, Trussell, Gallegos, & Asam, 2015). In a meta-analysis of 74 studies on the effectiveness of educational technology on mathematics achievement in the K-12 classroom, Cheung and Slavin (2013) found that technology had a positive, though moderate, effect.…”
Section: Introductionmentioning
confidence: 99%
“…In kindergarten through grade 12 mathematics education, technology is viewed as an integral part of instruction. There is evidence to support the positive impact technology has on mathematics achievement (Cheung & Slavin, 2013;Eyyam & Yaratan, 2014;Ojose, 2009;Schacter, 1999;Weaver, 2000;Zhang, Trussell, Gallegos, & Asam, 2015). In a meta-analysis of 74 studies on the effectiveness of educational technology on mathematics achievement in the K-12 classroom, Cheung and Slavin (2013) found that technology had a positive, though moderate, effect.…”
Section: Introductionmentioning
confidence: 99%